2020
DOI: 10.1186/s12884-020-03242-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal sex and maternal insulin resistance during mid-pregnancy: a retrospective cohort study

Abstract: Background Recent studies have suggested that fetal sex influences maternal glucose and insulin metabolism during pregnancy. We examined whether fetal sex is associated with maternal insulin resistance and the β-cell function during mid-pregnancy. Methods This retrospective study included singleton pregnant women who underwent a 75-g oral glucose tolerance test (OGTT) at 24–34 weeks of gestation due to positive diabetic screening. In addition to plasma glucose (PG), we measured plasma insulin during the OGTT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…In this study we have found pregnant women carrying male fetuses had lower fasting circulating glucose and insulin concentrations than those carrying females at around week 28 of pregnancy. Surrogate indices also suggest that those carrying male fetuses were more insulin sensitive, which is consistent with some [ 15 , 25 ] but not all [ 16 , 17 ] published studies. We also found that women carrying male fetuses had higher insulin disposition indices, suggesting higher insulin secretion for their degree of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study we have found pregnant women carrying male fetuses had lower fasting circulating glucose and insulin concentrations than those carrying females at around week 28 of pregnancy. Surrogate indices also suggest that those carrying male fetuses were more insulin sensitive, which is consistent with some [ 15 , 25 ] but not all [ 16 , 17 ] published studies. We also found that women carrying male fetuses had higher insulin disposition indices, suggesting higher insulin secretion for their degree of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 88%
“…As examples of this, systematic reviews and meta-analyses of individual studies, as well as certain individual studies, have shown that mothers carrying male fetuses are more likely to develop gestational diabetes (GDM) than those carrying female fetuses [ 12 14 ]. However, in one recent study, independent of GDM risk, markers of insulin resistance were lower in pregnant women carrying male fetuses [ 15 ]. An earlier study failed to find a fetal sex effect on maternal insulin sensitivity [ 16 ], instead finding mothers carrying male fetuses having higher circulating glucose concentrations but lower pancreatic β -cell function.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of 877 women, Geng et al [ 31 ] found higher fasting blood glucose and lower HOMA-β, a measure for β-cell function, in the second trimester of pregnancies with male fetuses. By contrast, Yamashita et al [ 32 ] and Xiao et al [ 33 ] observed higher maternal insulin resistance in pregnancies with female fetuses at 24-28 weeks gestation. Measuring fasting blood glucose longitudinally throughout pregnancy in a cohort including only overweight and obese women, Rafferty and colleagues observed no effect of fetal sex [ 34 ].…”
Section: Adaptation and Disruption Of Maternal Glucose Metabolism Depends On Fetal Sexmentioning
confidence: 91%
“…This was inconsistent with previous results from a singleton pregnancy cohort study (n = 299) showed that after adjustment for several demographic and clinical factors, including those related to MetS, a female fetus, compared to a male fetus, may be signi cantly more associated with maternal insulin resistance (P = 0.001) [21]. A previous retrospective study including 617 singleton pregnant women (mean age, 32.4 ± 4.9 years) suggested that after adjustment for various diabetes-related factors, insulin resistance was signi cantly higher and insulin sensitivity was lower in the female group than in the male group [22]. Young women with gestational diabetes have a high risk of developing type 2 diabetes for life.…”
Section: Discussionmentioning
confidence: 98%